‘A beggar has no choice' A Mixed Approach Exploring Blended Finance for Africa's Infrastructure - Wildschutt-Prins, Alvino (Graduate School of Business (GSB), 2021)
The United Nations estimated that to achieve the Sustainable Development Goals globally, they require approximately USD6 trillion per annum, totalling between USD90 to a USD100 trillion of investments needed over the 15 years. African countries are struggling to finance their infrastructure development needs and require innovative solutions to finance their infrastructure gaps. The African Development Bank noted that Africa's infrastructure needs can be estimated between USD130 and USD170 billion per annum with an estimated financing gap of USD68 billion to USD108 billion. Blended finance received international attention during the Third International Conference on Finance for Development in 2015 when it was mentioned in the adopted resolution report dubbed the Addis Ababa Action Agenda (here forth the Addis Agenda). The overall objective of this study is to explore the private sector participation investing in economic infrastructure in Africa and the public sector's understanding of blended finance. The research also focuses on the role of multi-and bilateral development banks in mobilising the private sector and the government support required to attract private sector participation investing in infrastructure projects For this study, the Convergent Parallel Design mixed research method is employed where both the quantitative and qualitative data are collected concurrently or in the same phase. The World Bank PPI database is used as the primary quantitative data source, while nine qualitative indepth interviews were conducted. The results from the multiple linear regression model indicate that projects with multi-lateral development bank' support are characterised by lower private sector participation in infrastructure investments in Africa. Furthermore, countries receiving concessional support from the International Development Association (IDA) are receiving lower private sector participation in their projects. In-depth interviews with public sector officials indicated that most of the officials had an overall understanding of blended finance in line with current market definitions. Officials, however, were not convinced with the use of concessional funding and loans in the blended finance structure due to the conditions precedents which came with it but felt like they had no choice but to accept these conditions due to the needs of the countries and the project involved. Informed by the findings of the study, the study recommends that blended finance should be localised for the African context and makes key policy recommendations linked to the OECD principles for blended finance.